Decreased atherogenic response to dietary cholesterol in pigeons after stimulation of cholesterol catabolism in early life. - Subbiah, M T (1983)
Cholesterol catabolism was stimulated in 6-wk-old White Carneau pigeons using a laboratory stock diet containing 1.3% cholestyramine resin. After 8 wk on this diet the animals were returned to control stock diet (no resin) for another 8-wk period. When subsequently challenged with a diet containing 0.5% cholesterol, cholestyramine-pretreated pigeons exhibited significantly lower serum cholesterol level when compared with controls and this "hyporesponder" behavior persisted throughout the study period. Furthermore, the aorta of cholestyramine-treated animals exhibited significantly (a) lower prevalence and severity of atherosclerosis and (b) lower cholesterol content. These studies demonstrate for the first time that enhancement of cholesterol catabolism in early life improves resistance to diet-induced atherosclerosis in later life in this avian model.